Deformation Characteristics and Control Technology of Roadway in Water-Rich Soft Rock. (4th May 2022) - Lin, Weiguo; Cheng, Jianliang; Li, Dalei; Dang, Haibo
Abstract : Jurassic soft rocks are the main coal-bearing strata in western mining areas, which are rich in water and high in expansive minerals. The roof and floor of the coal seam are easily muddied and disintegrated when affected by water, and heave floor of roadway in soft rock has become one of the problems that restricts the safety and efficient production of coal mines in western mining areas. It is not ideal for the effect of the traditional roadway control theory on geological soft rock roadway support, and the deformation is difficult to control. Take the tailgate of 11506 working face of a coal mine in the western mining area as the research background. This surrounding rock conditions and the deformation characteristics of the roadway in tailgate of 11506 working face were analyzed systematically, and the optimization design of the support scheme of the water-rich soft rock roadway was carried out by using theoretical analysis and numerical simulation. The application of the support in the tailgate of 11506 working face was carried out. The results show that slip of the two sidewalls, support failure, stress concentration, and floor heave were failure characteristics in water-rich soft rock roadway. The optimization of the roadway section, thin guniting of the roadway surface, optimization of support components, and gradient support could effectively achieve the control of soft rock roadway deformation. The maximum floor heave during the roadway deformation monitoring period was 230 mm, which decreased about 75% compared with original support. The influence range of the advance abutment stress is 0 60 m, of which 0 30 m is the serious influence area. The research results have good engineering practice significance for the control of bottom bulge of the soft rock roadway in this coal mine and western mining area.